Operational Cost Budget Planning and Supervision System at PT Asuransi MNC Life Assurance - Zulia Rifda Daulay; Khairatun Nazah (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the planning and monitoring of the operational cost budget for PT MNC Life Assurance and the role of the budget in planning and monitoring these costs. As well as measuring the effectiveness of planning and tracking operational expenses. This study uses a quantitative descriptive method. And to obtain data, the author uses data collection techniques in the form of interviews and observations. At the same time, the types of data used in this research are primary and secondary. Based on the results of calculations and data collection, planning and oversight of the budget succeeded in preparing and planning the budget properly until the realization stage and was included in the practical category.